Strategy to Improve the Quality of Management Information Systems and Work Environment on Employee Performance - Teguh Nada Firmansyah; Ade Albayan; Agus Sumarna (Lafadz Jaya Publisher, 2024)
This research is motivated by the lack of management information systems for employees, so data is needed related to strategies for improving the quality of management information systems and the work environment on employee performance. This type of research uses field research, with a qualitative approach. The results of this research show that in the management information system and work environment the key to employee performance is good communication. Where this communication can obtain clear and accurate information, if in a company there is no good communication then the information system will be in disarray without direction. The essence of the strategy to improve the quality of information systems and the work environment on employee performance is communication and cohesion between teams to become one goal.